Epidemiology and vaccine of porcine epidemic diarrhea virus in China: a mini-review - SUN, Dongbo (J Vet Med Sci, 2015)
Porcine epidemic diarrhea (PED) is an intestinal infectious disease caused by porcine epidemic diarrhea virus (PEDV); manifestations of the disease are diarrhea, vomiting and dehydration. Starting from the end of 2010, a PED outbreak occurred in several pig-producing provinces in southern China. Subsequently, the disease spread throughout the country and caused enormous economic losses to the pork industry. Accumulating studies demonstrated that new PEDV variants that appeared in China were responsible for the PED outbreak. In the current mini-review, we summarize PEDV epidemiology and vaccination in China.